Reuse oriented approach for reliable software product / Maziah Abdul Hamid - Abdul Hamid, Maziah (2005)
Software reuse oriented approach is an approach where the reuse of component in software development phases such as coding, people, and architecture. In order to implement reuse in an organization, many challenges must be face by the developer. Then, managing support is also one of the important things in implementing reuse. It is because; they are the one who giving cost to develop reuse. The objectives of this paper is to identify benefit using reuse oriented approach in an organization and to proposed architecture of the reuse oriented approach. Then, the findings gathered from the research is, the benefits that the most organization experience is shorten software development project and reduce cost of software development project. Then, the architecture proposed in this paper is called Reuse Engineering Life Cycle. It is based on the waterfall model, but in order to incorporate reuse, reuse repository, domain analysis and domain model are added. Furthermore, for formal reuse oriented approach, management support is vital, as well as the management of the reuse repository and the research on the reuse component being made by expert in domain analysis.